The causal dynamics between renewable energy, real GDP, emissions and oil prices: evidence from OECD countries - Apergis, Nicholas; Payne, J. (Routledge, 2014)
This study extends the empirical literature on the determinants of renewable energy consumption in the case of 25 OECD countries for the period 1980–2011. Preliminary analysis suggests the presence of cross-sectional dependence within the panel data. As a result, second-generation panel unit root tests of Smith et al. (2004) and Pesaran (2007) are undertaken to find the respective variables that are integrated of order one. Panel cointegration and error correction modelling reveal that a long-run relationship exists between renewable energy consumptionper capita, real GDP per capita, carbon dioxide emissions per capita and real oil prices. The long-run elasticity estimates are positive and statistically significant for real GDP per capita, carbon dioxide emissions per capita and real oil prices. The panel error correction model shows that a feedback relationship exists among the variables.